Co-Morbid Depression in Neuropathic Pain Sufferers: Prevalence and Effect on Quality of Life - Naveed Ahmed Durrani, Sumara Tabassam, Saqib Bajwa, Muhammad Hasan Wasim, Abdul Wasay Toor, Mufassar Nishat (Pakistan Journal of Medical & Health Sciences, 2023)
The treatment of neuropathic pain is notoriously challenging, and this is often attributed to the psychiatric comorbidity that is commonly misunderstood as being the primary cause of the patient’s suffering. Our study aimed to determine the relationship between depressive symptoms and the characteristics of neuropathic pain (NP), on the one hand, and quality of life (QoL), on the other hand, in a group of individuals who sought treatment for neuropathic pain (NP) regardless of the etiology of their condition. NP is a type of pain that is caused by damage to the nerves in the body. Study Pace: Kulsoom International Hospital Islamabad Study Duration: 6months (Feb 2021 to July 2021) Methods: We conducted a study with 60 individuals who came in seeking advice for neuropathic pain. The study was a cross-sectional design. We evaluated these participants based on their levels of five different parameters: their levels of neuropathic pain, as measured by DN4, their levels of pain intensity, as measured by EVA, their levels of anxiety and depression, as measured by the HADS, and their levels of quality of life. Results: The participants’ average age was 55.23 ± 20.67 years, the ratio of males to females was 0.54. The mean age of the people who took part in the study was 55.23 years. The three conditions that were seen most commonly as causes of neuropathic pain were postherpetic pain, carpal tunnel syndrome, and diabetic neuropathy. Depression affected the mental health of 64.9% of persons, while anxiety was a problem for 70.5% of individuals. The quality of life was significantly lower than expected given the average scores of 34.82 on the SF-12 physical subscale and 38.26 on the SF-12 mental subscale. On the BPI, the total mean score was 5.60, and the standard deviation was 1.77. Patients with high DN4 scores showed a significantly increased risk of becoming depressed (p = 0.024), compared to patients with lower DN4 values. This was demonstrated to be the case by the fact that there was a statistically significant positive association between the depression score and the level of pain (p = 0.001, r = 0.41). Patients who were diagnosed with depression were found to have a poor quality of life using both the SF-12 and the BPI. Conclusion: Given the impact that depression has on the components of neuropathic pain as well as quality of life, screening for this comorbidity ought to be a part of the baseline assessment for ND.